PROSES INTEGRASI DAN TERLEPASNYA TIMOR-TIMUR TERHADAP INDONESIA - Agus Rustamana; Anggi Ghefira S; Divino Narendra (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The history of East Timor is a history of conflict in a region. East Timor is a newly established country after successfully breaking away from the Unitary State of the Republic of Indonesia, through a poll on August 30 1999. This opinion poll was carried out because there were many conflicts occurring in East Timor, human rights violations continued to occur. This is because long before the country of Timor-Leste was formed, there were many conflicts and contradictions that occurred in the East Timor region. The long history of the conflict that occurred in East Timor will be discussed by the author in this journal. It is as if the history of the conflict that occurred in East Timor will never end. The most striking conflict, among others, was the conflict that occurred between the Fretilin political party in East Timor which was fighting for its independence and the Indonesian government which thought that the Fretilin Party was a radical party which had to be suppressed as soon as possible with the movement of Indonesian military troops. However, this gave rise to many violations. human rights towards the people of East Timor. This problem was immediately followed up when Indonesia experienced a change of President from President Suharto and Bj. Habibie. With the firmness of President Bj. Habibie, who was not too resistant to Timor-Leste's secession, finally created a poll for the people of Timor-Leste. In this opinion poll, there are 2 options, namely special autonomy but remaining a part of Indonesia or independently choosing to separate from Indonesia. The result obtained was that in the end the opinion deliberation was won by the parties who chose to be independent and separate from Indonesia.